Facade, Darabshaw House - Ghosh, Ayan (2023)
Darabshaw House is a corner building at the intersection of Shoorji Vallabhdas Road and N Morarji Road. It was earlier the site of the Regent Hotel, one of two hotels in Ballard Estate (Grand Hotel is the other) at the time when it was built. It now houses the offices of Condé Nast India.